Effect of different co-solvents on properties of Ibuprofen PVA gels - ياسين وعد; لمى الهوشي (Latakia University Journal -Medical Sciences Series, 2023)
The aim of this study is to prepare topical Ibuprofen PVA gels and studying the effect of Ibuprofen solubility in different co-solvents on gel properties (visual inspection, pH test, content uniformity, spreadability and in-vitro release). Homogeneous gels were obtained with suitable texture and pH for topical application. In order to improve the solubility of poorly soluble ibuprofen in water, the effect of co-solvent (concentration and type) on the solubility of ibuprofen was studied. It was observed that increase of ethanol concentration improved both the solubility and the released amount of Ibuprofen. On the other hand, PG was superior to ethanol at same concentration (5%) for solubility enhancementt. Also, it was found that spreadability was decreased by increasing ethanol concentration.The formula F7 which contains Et20%+PG5% as co-solvents has the highest value of solubility (0.54 mg/ml) and the highest released amount of Ibuprofen (98%). Therefore F7 is considered to be candidate for acute pain relief.